The Students’ Perception Toward TOEFL Test At SMA Negeri 2 Pematangsiantar - Rumahorbo, Leta Denarosana; Damanik, Novry Yohanna; Hutahaean, Rossa Ito; Manurung, Novita Gresiana; Sianturi, Oktavianti; Sinaga, Yanti Kristina; Panggabean, Eva Saryati; HS, Sahat Renol; Sirait, Esti Marlina (Pengabdian Masyarakat Sumber Daya Unggul, 2024)
This study aims to assess the efficacy of an introductory TOEFL training program designed for high school students, focusing on improving linguistic competence and revealing the nuances of the TOEFL exam. The primary objective is to evaluate the impact of TOEFL introductory training on secondary school students' readiness for advanced studies. A quantitative descriptive approach was employed to evaluate the effectiveness of TOEFL introduction outreach activities. The study focused on female students in class XII Mia-4 at SMA N 2 PEMATANGSIANTAR. Data was collected through TOEFL introduction outreach activities, including reading test sheets, and analyzed quantitatively by counting correct and incorrect answers. The research instrument used was a reading test sheet prepared by the research team. The study involved three stages: preparation, implementation, and evaluation. The population for this study comprised all female students in class XII Mia-4 at SMA N 2 PEMATANGSIANTAR. The sample included 34 students who participated in TOEFL socialization activities on January 11, 2024. The TOEFL socialization activities conducted on January 11, 2024, at SMA N 2 Pematangsiantar resulted in positive outcomes. The self-introduction, TOEFL material presentation, and question-and-answer session were conducted smoothly, creating a friendly and interactive atmosphere. The findings from the reading test question sheets revealed that most students understood the TOEFL test, with 28 out of 34 successfully filling in the questionnaire with different answers. However, challenges included students' initial confusion about the material and a lack of understanding of the benefits of the TOEFL test. The presenter addressed these challenges by providing explanations and encouraging students to be more active in their studies to enhance their knowledge of the TOEFL test.